Zmienność kursu walutowego w strategii wprowadzenia euro - Franek, Sławomir (Exchange rate flexibility in the strategy for adopting the euro, 2006)
The article discusses the role of exchange rate in the fulfilling of nominal convergence criteria in the three countries of UE: Poland, Hungary, Czech Republic. The different methods of calculating the exchange rate flexibility show, that Polish zloty is the most volatile currency, what can make difficulties with entering the euro zone.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 93-100